Atrial natriuretic peptide gene - a potential biomarker for Long QT syndrome - Qureshi, Sameera Fatima; Ali, Altaf; Venkateshwari, Ananthapur; Rao, Hygriv; Jayakrishnan, M. P.; Narasimhan, Calambur; Shenthar, Jayaprakash; Thangaraj, Kumarasamy; Nallari, Pratibha (Technische Universität Dortmund, 2014)
This study highlights the possible implication of NPPA (natriuretic peptide precursor A) gene in the etiology of Long QT syndrome (LQTS) by population-based as well as familial study. Three SNPs of NPPA- C-664G, C1363A and T1766C were examined by molecular analyses in LQTS, controls and first degree relatives (FDRs). This study revealed a possible association of 1364 C>A SNP ‘C’ allele with LQTS (p = 0.0013). All three SNPs were in tight linkage disequilibrium. The familial study highlights the association of NPPA SNP with cLQTS and implicating it as a potential biomarker in South Indian population.
EXCLI Journal ; Vol. 13, 2014
Keywords: atrial natriuretic peptide; Long QT syndrome; cardiogenesis; biomarker; polymorphisms; 610